2023
DOI: 10.1108/tlo-09-2021-0115
|View full text |Cite
|
Sign up to set email alerts
|

Transformational leadership and learning flows

Abstract: Purpose This study aims to examine how transformational leadership impacts learning flows that are critical for enhancing the learning capabilities of organizations. Design/methodology/approach Data were collected from 502 employees of business organizations located in India. A cross-sectional design was adopted, and partial least squares structural equation modeling (PLS-SEM) was used for data analysis. Findings Transformational leadership behavior positively influences feed-forward learning flows in orga… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 73 publications
0
5
0
Order By: Relevance
“…Hariharan & Anand (2023) found that transformational leadership strengthens followers’ learning stocks and that such learning stocks lead to increased feed-forward learning flows. When there is transformational leadership and the learning stock is high, transformational leadership stimulates feed-forward learning flows more intensely.…”
Section: Transformational Leadership For Organizational Transformationmentioning
confidence: 99%
See 3 more Smart Citations
“…Hariharan & Anand (2023) found that transformational leadership strengthens followers’ learning stocks and that such learning stocks lead to increased feed-forward learning flows. When there is transformational leadership and the learning stock is high, transformational leadership stimulates feed-forward learning flows more intensely.…”
Section: Transformational Leadership For Organizational Transformationmentioning
confidence: 99%
“…Hariharan & Anand (2023) address learning flows and how they can be influenced by transformational leadership. Optimizing learning flows is key to improving an organization’s learning capability and its competitive advantage.…”
Section: Transformational Leadership For Organizational Transformationmentioning
confidence: 99%
See 2 more Smart Citations
“…Transformational leadership facilitates the growth of the work teams' learning capacity through intellectual stimulation (L opez-Zapata, Hincapi e-Montoya, & Zuluaga-Correa, 2017) and influences an organization's ability to pursue exploitation and exploration innovation by promoting their ambidexterity (Jansen, Van Den Bosch, & Volberda, 2005). Recent studies have found that transformational leadership fosters feed-forward learning flows through the development of individual learning stock (Hariharan & Anand, 2023). The performance of work teams tends to improve due to the organizational climate and job satisfaction promoted by the transformational leadership style (Gaviria-Rivera & L opez-Zapata, 2019).…”
Section: Theoretical Frameworkmentioning
confidence: 99%